COMPLIANCE WITH MEDICATION TREATMENT BY PEOPLE WITH ANXIETY DISORDER - Ligiane Paula da Cruz de Sousa; Kelly Graziani Giacchero Vedana; Adriana Inocenti Miasso (Universidade Federal do Paraná, 2016)
In this study, the factors related to compliance with the prescribed drugs therapy are verified among people with anxiety disorder. Quantitative, cross-sectional, descriptive study, involving 161 patients from a mental health service in a city of the state of São Paulo, between January 01st and December 31st 2012. Patient histories were reviewed and the Treatment Adherence Measure, Beck Anxiety Inventory and a sociodemographic script were used. Most participants were considered compliant with the drugs. No statistically significant differences were evidenced between compliance and the research variables. The high percentage of participants using benzodiazepines over a long period is highlighted, suffering from moderate and severe anxiety despite the medication compliance and who were unaware of the prescribed medication dose. This study appoints elements that interfere in the safety of the drug treatment for people with anxiety disorder for whom intervention is possible, contributing to improve their treatment.